PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT PACIFIC REMOVINDO DI JAKARTA - Agustina Mogi; Arief Rahman Maulidi (Al Hasanah Barokah Foundation, 2026)
This study aims to determine the effect of compensation and work discipline on employee performance at PT. Pacific Removindo in Jakarta. The research uses a quantitative associative approach with a survey method. The sample consists of 76 respondents who are employees of PT. The results showed that partially, compensation has a positive and significant effect on employee performance with the regression equation Y = 23.966 + 0.477 X1, t-value = 2.957 > t-table = 1.996, and a significance of 0.004. Work discipline also has a positive and significant effect on employee performance with the regression equation Y = 12.155 + 0.705 X2, t-value = 5.456 > t-table = 1.996, and a significance of 0.004. Simultaneously, compensation and work discipline have a positive and significant effect on employee performance with the regression equation Y = 7.329 + 0.266 X1 + 0.571 X2. The F-value is 32.204 > F-table = 3.122 with a significance of 0.000, and the coefficient of determination (R²) is 0.469 or 46.9%. This means that 46.9% of the variation in employee performance can be explained by compensation and work discipline, while the remaining 53.1% is explained by other variables not examined in this study. The results show that compensation has a positive and significant effect on employee performance, and work discipline also positively and significantly affects employee performance. Simultaneously, compensation and work discipline have a positive and significant influence on the performance of employees at PT. Pacific Removindo.